Opinion leadership, threats, and enhancers to social cohesion and unity of South Africans and African immigrants in the post-apartheid era - Maseng, Jonathan Oshupeng (Frontiers in Human Dynamics, 2025)
Most existing studies document the sporadic incidences of Afrophobia, xenophobia, color-blind xenophobia, and sibling fights within South Africa. These studies consistently present citizens as active players in anti-immigrant attitudes, actions, and sentiments. However, there appears to be a scarcity of literature in the South African context that focuses on how opinion leaders affect social cohesion and unity between South Africans and African immigrants. Additionally, although some research has examined factors that influence social cohesion between these groups, there is a lack of comprehensive studies on the specific role of opinion leaders in enhancing or threatening this cohesion. The paper seeks to respond to the question what are the effects of opinion leaders in enhancing or threatening social cohesion between South Africans and African immigrants? Through the use of exploratory and case study research designs, as well as qualitative methods and thematic analysis, this paper seeks to explore how opinion leaders such as the South African government and its officials, politicians, political parties, and the media, affect social cohesion between South Africans and African immigrants. The work argues that opinion leaders can positively and negatively influence social cohesion between these groups. The paper recommends that political parties, government officials, and the media play a key role in fostering social cohesion between African immigrants and South Africans. This has significant implications for enhancing unity in South African communities composed of African immigrants and South African nationals.